Virtual Worlds for academic, organizational, and life-long learning - ViWo 2009) - for Papers, Call (International Journal of Advanced Corporate Learning (iJAC), 2008)
This special track will take place during the IMCL 2009 in Amman, Jordan (April 22-24) as a special program item.The Special Track ViWo 2009 provides an interdisciplinary forum for international scientists and practitioners to discuss various aspects of learning and training in virtual worlds.